Per Capita Health Expenditure at a Municipal Hospital: Perspective from a General Practice Hospital in Rural Nepal - Agrawal, Pawan Kumar Bajaj; Giri, Baburam; Gupta, Priyanka; Nepali, Anjan; Parajuli, Suraj (Journal of Karnali Academy of Health Sciences, 2025)
Background: The Government of Nepal has been strengthening the primary care and fulfilling the commitment of universal health coverage by upgrading and establishing municipal hospitals. These hospitals are expected to be affordable and accessible. It is necessary to understand the health expenditure at these primary centers to reflect upon the productivity, especially in low income countries like Nepal struggling with adequate expenditure in health. Therefore, we aimed to reflect upon the temporal trend of per capita health expenditure in a rural municipal hospital. Methods: The descriptive combined cross-sectional study was conducted in Amppipal Municipal Hospital, in rural Gorkha with catchment population of 37,409, over duration of five fiscal years. Yearly records of expenditure and total number of clients were used to infer per capita expenditure. The total number of emergency patients, inpatients and surgeries performed were documented in order to reflect upon their impact. Result: The total annual clients visiting the hospitals increased over the years from 19,062 in FY 2017/18 to 28,249 in FY 2021/22. The median contribution of emergency patients and admitted patients among total clients over the years was 3.1% and 5.2% respectively. Surgeries, including minor ones, were performed in 3.7% of the total yearly clients.The per capita expenditure increased from NPR 1,217 in FY 2017/18 (USD 9.3) to NPR 1,438 (USD 11.0) in FY 2021/22, one United States dollar being equivalent to one hundred and thirty Nepali rupees. The median per capita expenditure was NPR 1,303 (USD 13.0). Conclusion: Our study suggested the increasing trend of per capita health expenditure over five years duration in a primary care municipal hospital in Nepal, with overall increase of 18.15%. The study would be helpful in budgeting and evaluating the productivity of these primary care institutions.